Analysis of Factors that Influence Interest in Using the SI APIK Application (Study of MSMEs in Mataram City) - Jurati, Jurati; Effendy, Lukman; Nurabiah, Nurabiah (Journal Of Accounting Management Business And International Research, 2024)
This research aims to analyze the factors in the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2) model that influence interest in using the SI APIK application. This type of research is associative research using a quantitative approach. The data source in this research is primary data by distributing questionnaires to owners, financial staff, marketing staff and cashiers at MSMEs. The research sample was MSMEs in Mataram City which were assisted by BI NTB with a total of 41 respondents. The data analysis procedure in this research uses the SmartPLS software application version 4.0. The results of this research show that the variables performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, price value, and habit do not affect behavioral intention SI APIK application. The implication of this research is that Bank Indonesia as the maker of the SI APIK application should assist each MSMEs one by one in implementing the SI APIK application. The purpose of mentoring in this context is to directly assist and guide MSMEs in using the SI APIK application.